Las finanzas personales y contribución familiar en los pobladores de la comunidad nativa Vencedor río Pisqui Contamana año 2022 - Peña Escamilo, Frank (2023)
The objective of the research was to determine the relationship between personal finances and family contribution, whose study was descriptive-correlational and non-experimental design with a population and sample made up of 100 inhabitants, to whom the questionnaire was applied, where results were obtained. of personal finances being qualified as regular by 27%, due to the fact that the inhabitants of the community reveal that they sometimes record their income and expenses; they also sometimes plan their expenses based on the income obtained from their work. For its part, the level of family contribution is regular at 30%, since income from work has sometimes allowed them to be outside the poverty line. Finally, it was determined that there is a relationship between the study variables, being corroborated by a coefficient and significance of (r=0.764; p=0.000).